DEVELOPMENT OF AGRICULTURAL PRODUCTION IN THE AREA OF DRAINAGE RECRUITMENT IN THE CONDITIONS OF CLIMATE CHANGE - Воропай, Галина (SWorldJournal, 2020)
The paper determines that the conduct of modern agricultural production in the area of drainage reclamation is manifested in changes in the specialization of farms in almost all regions of the humid zone of Ukraine, which began in the 90s of last century.